Evolution of morphological but not aggressiveness‐related traits following a major resistance breakdown in the poplar rust fungus, Melampsora larici‐populina. (16th October 2020) - Maupetit, Agathe; Fabre, Bénédicte; Pétrowski, Jérémy; Andrieux, Axelle; De Mita, Stéphane; Frey, Pascal; Halkett, Fabien; Hayden, Katherine J.
Abstract: Crop varieties carrying qualitative resistance to targeted pathogens lead to strong selection pressure on parasites, often resulting in resistance breakdown. It is well known that qualitative resistance breakdowns modify pathogen population structure but few studies have analyzed the consequences on their quantitative aggressiveness‐related traits. The aim of this study was to characterize the evolution of these traits following a resistance breakdown in the poplar rust fungus, Melampsora larici‐populina . We based our experiment on three temporal populations sampled just before the breakdown event, immediately after and four years later. First, we quantified phenotypic differences among populations for a set of aggressiveness traits on a universally susceptible cultivar (infection efficiency, latent period, lesion size, mycelium quantity, and sporulation rate) and one morphological trait (mean spore volume). Then, we estimated heritability to establish which traits could be subjected to adaptive evolution and tested for evidence of selection. Our results revealed significant changes in the morphological trait but no variation in aggressiveness traits. By contrast, recent works have demonstrated that quantitative resistance (initially assumed more durable) could be eroded and lead to increased aggressiveness. Hence, this study is one example suggesting that the use of qualitative resistance may be revealed to be less detrimental to long‐term sustainable crop production.